INOVASI DALAM MANAJEMEN PENDIDIKAN: IMPLEMENTASI PENGGUNAAN CANVA SEBAGAI MEDIA PEMBELAJARAN - Ummul Khaira; Hadiyanto; Rusdinal (STKIP Subang, 2023)
To produce quality learning, good management is needed that can support the achievement of educational goals. In management at school, the principal has an important role. The principal serves as a motivator and supervisor of teachers so that they are able to modify the learning that is carried out at school. One of them is the use of technology as a learning medium that is able to facilitate teachers in teaching and provides opportunities for students to be creative according to their imagination. This research is to explore the use of Canva as a learning medium in elementary schools and to discuss the benefits and potential of using Canva in the learning process. The research was conducted using a descriptive descriptive approach with the results of the research namely obtaining information that the supporting factors in implementing Canva as a learning medium include: 1) Infrastructure that supports the presence of a number of chromebooks in schools. 2) Students have a high curiosity and passion for learning. 3) The Canva app is easy to use on PC and mobile devices. 4) Videos for learning can be seen repeatedly. Implementation of Canva as a learning medium in elementary schools has a positive impact on students, including students being able to understand material easily, students are more enthusiastic about learning, and being able to train students to be confident by presenting material through learning media .